Increasing the efficiency of attacking strike after a negative receipt of the ball in volleyball - Nikolaeva O.V. ,; Minina L.N. ,; Ramzaitseva A.A. ,; Sergazinova M.A. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop means to increase the efficiency of the attacking blow after a negative ball reception among qualified volleyball players. Methods and structure of the study. The pedagogical experiment involved a survey of trainers and pedagogical observation using the Data Volley computer program. Results and conclusions. It was revealed that it is advisable to include specially designed exercises in the training process of qualified volleyball players to improve attacking actions after a negative ball reception. It was experimentally established that the effectiveness of an attacking blow after a negative reception of the ball increased (before the experiment 25.6 ± 6.9%, after 41.7 ± 7.9%), which made it possible to increase the effectiveness of all attacking blows during competitive activity (before the experiment 46.6±4.6%, after 51.0±4.2%).